Politics, symbols and the public sphere the protests against nuclear weapons in Britain and West Germany, 1958-1963 - Nehring, Holger 1974- (Zeithistorische Forschungen, 2005)
This article discusses key aspects of the symbolic politics of the British and West German anti-nuclear-weapons movements in the late 1950s and early 1960s. More specifically, it examines the interaction between protest, politics, the media and the public sphere. It proposes two analyses of the protests: first, as the creation of a public sphere by means of "street politics" and, second, as a key to establishing an emotional community of protesters both in a national and transnational context. The media played a crucial role by enabling isolated protests to be perceived as parts of broader movements. The article argues that protests in both countries by and large adhered to, rather than transcended, the dominant national cultural codes. These movements thus exemplify the ways in which international relations, transnational links and national protest traditions interact.